Severe growth retardation, delayed bone age, and facial dysmorphism in two patients with microduplications in 2p16 → p22. Issue 12 (24th September 2013) - Blassnig‐Ezeh, Anya; Bandelier, Claude; Frühmesser, Anne; Revencu, Nicole; Krabichler, Birgit; Beauloye, Véronique; Ravoet, Marie; Fauth, Christine; Zschocke, Johannes; Simma, Burkhard; Kotzot, Dieter
Abstract: Interstitial duplications of the short arm of chromosome 2 have been rarely described. Here, we report on two unrelated patients with overlapping chromosome 2p16 → p22 de novo microduplications found by SNP‐array analysis. The affected individuals were an 8‐year‐3‐month‐old boy with a direct duplication of approximately 14.6 Mb harboring 63 genes, and a 12‐year‐old girl with a direct duplication of around 9.6 Mb harboring 48 genes. Both patients have severe growth retardation, delayed bone age, prominent veins on trunk and extremities, total IGF1 level in the low range, mild developmental delay, and facial dysmorphism such as relative macrocephaly, a broad and prominent forehead, and a large anterior fontanelle. Comparison with patients previously reported in the literature and in the DECIPHER 5.1 and ECARUCA databases indicates a common region of interest of around 1.9 Mb responsible for most of the features. Two candidate genes ( EPAS and RHOQ ), may be particularly relevant for the marked growth retardation and developmental delay. © 2013 Wiley Periodicals, Inc.